2001
DOI: 10.1002/j.2168-9830.2001.tb00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving First‐Year Engineering Education*

Abstract: In September of 1998, the College of Engineering at the University of Massachusetts Dartmouth (UMD) piloted an innovative, integrated, first‐year curriculum. It dramatically changed 31 credits across two semesters. The program was modeled after several previous successful undergraduate experiments at other universities such as those in the NSF Foundation Coalition and at Rensselaer Polytechnic Institute. The new program at UMD included This paper describes the new curriculum, some of the practical consideratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 5 publications
0
26
0
Order By: Relevance
“…978-1-4673-5261-1/13/$31.00 ©2013 IEEE Prior research in the first year of engineering has focused on an understanding of student success directly related to coursework [1], innovative curriculum design [2,3,4,5], and specific necessary components of the first year including a solid foundation in math [6]. Brannan and Wankat [7] looked at different components in the first year, including introductory courses.…”
Section: Methodsmentioning
confidence: 99%
“…978-1-4673-5261-1/13/$31.00 ©2013 IEEE Prior research in the first year of engineering has focused on an understanding of student success directly related to coursework [1], innovative curriculum design [2,3,4,5], and specific necessary components of the first year including a solid foundation in math [6]. Brannan and Wankat [7] looked at different components in the first year, including introductory courses.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar case, to motivate science and maths learning, two engineering courses were integrated with the calculus and physics sequence, to improve first-year engineering education and develop students' skills in oral and written communication. The researchers found that the performance of the students increased significantly on common final exams in both physics and calculus (Pendergrass et al 2001).…”
Section: Theories and Practice On Successful Coursesmentioning
confidence: 98%
“…Characteristics: Weekly assistance for students with good academic performance in previous years -answering questions 5 . Steps for implementing this support: A student from a previous year that demonstrates good academic performance is available to support the freshman student.…”
Section: Student Supportmentioning
confidence: 99%
“…Characteristics: Weekly teaching service -answering questions / performing exercises 5 . Steps for implementing technical staff support: an instructor is available once a week (8 h) to help the student solve exercises and explain physics concepts to clarify his/her doubts.…”
Section: Technical Staffmentioning
confidence: 99%
See 1 more Smart Citation